Yearbook Video 1985-1986 - San Luis Video Productions::::::::: (1985)
Footage from the 1985-86 school year, including footage of the Rose Parade float, Poly Royal, and Week of Welcome. [00:00:00] Introduction and aerial views of Cal Poly campus. [00:00:34] Videos of WoW groups [00:04:30] Students at football game [00:04:53] Cal Poly's Rose Float [00:05:00] Cal Poly football game [00:05:53] Girl's Volleyball game [00:06:17] Drama production [00:06:26] Clip of the sandwich shop [00:06:35] Inside classroom [00:07:00] Cal Poly dance program [00:07:32] Baseball game [00:07:48] Unidentified man giving speech [00:07:54] View of the beach and downtown [00:08:29] Swim team [00:08:35] Various locations around San Luis [00:08:43] Basketball Game [00:08:56] Softball game [00:09:10] Basketball victory celebration [00:09:15] Track meet [00:09:48] Students dance to live music on Dexter lawn [00:10:10] Women's recreational dancing [00:10:18] Students listen to live music on Dexter Lawn [00:10:35] Poly Royal [00:11:14] Women's synchronized swimming [00:11:20] Diving [00:11:27] Beach Races [00:11:52] Poly Royal [00:12:10] Fraternity's Luau [00:12:26] Parade around Cal Poly's campus [00:13:01] View of the ocean and pier [00:13:20] North Mountain dorms [00:13:35] People gathering on a lawn [00:13:52] Beach view [00:13:57] Cal Poly Rodeo [00:14:10] Students in various places around campus [00:14:40] WoW groups [00:15:21] Football game [00:15:39] Brief clips of live music, dance shows, sports games, rodeo [00:16:13] Student life on campus [00:17:22] Campus aerial [00:17:30] Commencement